Role of knowledge in the adoption of new agricultural technologies: An approach and an application - Jabbar, M.A.; Mohamed Saleem, M.A.; Gebreselasie, S.; Beyene, H. (Inderscience Publishers, 2003)
Empirical studies on agricultural technology adoption generally divide a population into adopters and nonadopters, and analyse the reasons for adoption or nonadoption at a point in time. In reality, technology adoption is not a one-off static decision, rather it involves a dynamic process in which information gathering, learning and experience play pivotal roles, particularly in the early stage of adoption. A conceptual framework for an adoption pathway is suggested in which farmers move from learning to adoption, to continuous or discontinuous use over time. The framework was applied to understand the adoption pathways for vertisol management technology in highland Ethiopia. Analysis of a sample of 585 households confirmed that a simple classification of farmers as adopters and nonadopters was inadequate to understand the adoption process. Rather, a multistage decision process in which farmers moved from learning to adoption to continuous or discontinuous use was more appropriate. The sets of factors that significantly influenced decisions to acquire knowledge about BBM, to adopt and then to use it continuously or discontinuously were different. The lag between learning and adoption, and the possibility of discontinuation and readoption, imply that a longer period will require for majority of the farmers to use the technology than if adoption was a one off decision leading to continuous use.